2020
DOI: 10.1111/hae.14101
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia care in China: Achievements in the past decade

Abstract: There is a large population of people with haemophilia in China. However, the development of haemophilia care in China lagged far behind developed countries and was unbalanced across different regions. With the establishment of the Hemophilia Treatment Center Collaborative Network of China (HTCCNC) in 2004 and its collaboration with the Chinese government, the World Federation of Haemophilia (WFH), non-profit foundations, industries, and experts from other countries, haemophilia care in China have made conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 41 publications
(53 reference statements)
0
34
0
Order By: Relevance
“…However, in many parts of the world, opportunities for prophylaxis are limited. In the past decade, China has established the Hemophilia Treatment Center Collaborative Network of China, which has made significant advances in hemophilia 8 . A real‐world study of 428 haemophilia patients based in a single centre in Tianjin showed that the proportion of children and adults receiving prophylaxis is significantly higher than a decade ago, from 2.0% (two patients) in 2012 to 66.7% (64 patients) in 2018, and from .4% in 2012 to 17.3% in 2018, respectively 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in many parts of the world, opportunities for prophylaxis are limited. In the past decade, China has established the Hemophilia Treatment Center Collaborative Network of China, which has made significant advances in hemophilia 8 . A real‐world study of 428 haemophilia patients based in a single centre in Tianjin showed that the proportion of children and adults receiving prophylaxis is significantly higher than a decade ago, from 2.0% (two patients) in 2012 to 66.7% (64 patients) in 2018, and from .4% in 2012 to 17.3% in 2018, respectively 9 .…”
Section: Introductionmentioning
confidence: 99%
“…China is a large country with an estimated haemophilia population of ~130 000. The Haemophilia Treatment Centre Collaborative Network of China (HTCCNC), an organisation with 120 member haemophilia treatment centres (HTCs), is dedicated to the development of haemophilia care in China 13 . With the efforts of HTCCNC and better medical insurance coverage for FVIII, an increasing number of patients with HA are now receiving FVIII replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hemophilia care capacity has increased continuously since 2004, when the Hemophilia Treatment Center Collaborative Network of China (HTCCNC) was established. The HTCCNC, comprises 120 centers throughout the country, playing a crucial role for hemophilia care provision [ 5 , 6 ]. Affordability and accessibility for hemophilia care have also been improved remarkably by the expansion of universal medical insurance coverage, which provides partial financial support for inpatient and outpatient treatment, drugs and diagnostic expenses.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the joint government—healthcare system efforts to treat hemophilia, the hemophilia care level in China lags behind developed countries [ 6 ]. In a comparative investigation of quality of life between China and nine other countries, Sun et al found that Chinese hemophilia patients received less prophylaxis treatment, faced greater difficulty in obtaining replacement factor products and were vulnerable to more annual bleeds [ 10 ].…”
Section: Introductionmentioning
confidence: 99%